Oligonucleotide-templated lateral flow assays for amplification-free sensing of circulating microRNAs. Issue 83 (26th September 2019) - Pavagada, Suraj; Channon, Robert B.; Chang, Jason Y. H.; Kim, Sung Hye; MacIntyre, David; Bennett, Phillip R.; Terzidou, Vasso; Ladame, Sylvain
Abstract : Low-cost detection of miRNA biomarkers from maternal blood is achieved via a highly sequence-specific templated reaction on nitrocellulose paper strips to enable early prediction of preterm birth in a minimally invasive manner. Abstract : Herein we demonstrate the first example of oligonucleotide-templated reaction (OTR) performed on paper, using lateral flow to capture and concentrate specific nucleic acid biomarkers on a test line. Quantitative analysis, using a low-cost benchtop fluorescence reader showed very high specificity down to the single nucleotide level and proved sensitive enough for amplification-free, on-chip, detection of endogenous concentrations of miR-150-5p, a recently identified predictive blood biomarker for preterm birth.